Alkoxy functionalized benzothiadiazole based donor–acceptor conjugated copolymers for organic field-effect transistors. Issue 15 (12th April 2021) - Comí, Marc; Patra, Dhananjaya; Yang, Rui; Chen, Zhihui; Harbuzaru, Alexandra; Wubulikasimu, Yiming; Banerjee, Sarbajit; Ponce Ortiz, Rocío; Liu, Yao; Al-Hashimi, Mohammed
Abstract : Benzothiadiazole (BT) and its derivatives have been widely used as strong acceptors for enhancing π-stacking and improving the charge carrier transport properties in optoelectronic applications. Abstract : Benzothiadiazole (BT) and its derivatives have been widely used as strong acceptors for enhancing π-stacking and improving the charge carrier transport properties in optoelectronic applications. We report the synthesis of five copolymers based on the acceptor 4, 7-bis(5-bromo-4-octylthiophen-2-yl)-5, 6-bis(octyloxy)benzo[ c ][1, 2, 5]thiadiazole copolymerized with thiophene (CP1 ), 3, 4-difluorothiophene (CP2 ), bithiophene (CP3 ), 3, 3′-difluoro-2, 2′-bithiophene (CP4 ) and selenophene (CP5 ) as the donor comonomers. Enhanced copolymer solubility and effective packing between the chains were obtained. All copolymers exhibited favorable optical and electrochemical properties with low band gaps and strong π–π intermolecular interactions. Computational studies on various repetitive units revealed the most stable conformations, dihedral angles, possible interactions and energy levels. OFET devices fabricated with the copolymers exhibited a maximum charge carrier mobility of 0.67 cm 2 V −1 s −1 for CP3 .